The Correlation of Growth Mindset and Speaking Ability - Suriyah, Eni; Adisti, Aprilian Ria (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
Growth mindset and students’ achievement have linearity in the previous studies. In EFL setting students’ achievement is related to English skills. Success in language learning is discovered by acquiring speaking ability. Thus this research aims to find out the correlation between students’ growth mindset and students’ speaking ability at the Second Semester Students of English Education Department of State Islamic University of Salatiga in t.rhe Academic Year 2021/2022. The methodology used in this study is quantitative method with correlational design. The techniques of collecting data are documentation and questionnaire. Data is analyzed in two ways. First, quantitative data was analyzed using statistical description and inferential descriptive. This study revealed that there is correlation between students’ growth mindset and students’ speaking ability. The value of Sig. (2-tailed) in the person correlation test is 0,027 which is bigger than 0,05 and it means that there is significant correlation between students’ growth mindset and students’ speaking ability. Meanwhile the correlation value is 0,27 that indicated the correlation is weak based on the degree of correlation table that correlation value between 0,21-0,40 is weak correlation. Further discussion is presented in this study.